Qualitative Study Of Nvivo-Based Concept Understanding In Lesson Study Learning In Climate Change Courses - Lisa Janesa Saputri; Nova Susanti; Rahma Dani (Universitas Muhammadiyah Gresik, 2025)
This research aims to explore students' achievement of understanding physics concepts through qualitative data analysis using NVivo. Education, as regulated in Law no. 20 of 2003 concerning the National Education System, aims to develop the potential of students to become individuals who have faith, noble character, knowledge and independence. In this context, learning physics does not only study theory but also applies practice to understand natural phenomena as a whole. The research method used is qualitative, with data sources in the form of learning media, materials and interactions during teaching and learning activities. Data analysis was carried out using NVivo, producing visualizations such as word clouds and word trees to understand the structure and meaning of the data. This study also discusses the use of NVivo and TBLA (Transcript-Based Lesson Analysis) in qualitative data analysis, which shows the effectiveness of data visualization in understanding the relationship between climate change and the agricultural sector. This research confirms the importance of understanding concepts in education and the contribution of NVivo in improving quality qualitative data analysis